Integrating Bowtie Analysis into Band Saw Maintenance - Tsapi, T. K.; Tongwa, M. K.; Soh, B. D. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2024)
Sawing machines used to cut raw materials to desired dimensions in industrial manufacturing operations are of great importance. Occupational injuries have occurred in the past as a result of failures in the risk management of these machines. In this paper, Bowtie analysis-based risk identification is developed based on the diagnosis of band saw cutting machine components. The results of the Bowtie risk assessment for hazards associated with the impeller, pump housing, saw blade, clamp, and seal pump were developed to structure the decision-making process with better information visualization. Hazards in the Bowtie were used to describe the root causes of failure (threats) that were identified, such as inadequate maintenance planning, foreign objects entering the pump, and inadequate maintenance. Based on the Bowtie diagrams, which capture the sufficient complexity of the real system behavior, the cutting tool was maintained following a corrective action plan that was developed. The assessment of the band saw performance rate after maintenance was 93%. This demonstrates that decision-makers can manage risk and reinforce a work culture that prioritizes actions to improve maintenance and safety outcomes using the Bowtie analysis method.